Pancakes, pancakes! - Carle, Eric. (New York : Simon & Schuster Books for Young Readers, 1990)
By cutting and grinding the wheat for flour, Jack starts from scratch to help make his breakfast pancake.
Reprint. Originally published: New York : Knopf, 1970.
Book Links (A.L.A.)
Booklist
Book Links (A.L.A.), November 1996
Booklist, June 2001
3.1
Keywords: Cooking -- Fiction; Pancakes, waffles, etc. -- Fiction; Cooking -- Fiction; Pancakes, waffles, etc. -- Fiction